Effects of soybean lipid infusion on triglyceride and unbound free fatty acid levels in preterm infants. (2nd October 2019) - Hegyi, Thomas; Kleinfeld, Alan; Huber, Andrew; Weinberger, Barry; Memon, Naureen; Joe Shih, Weichung; Carayannopoulos, Mary; Oh, William
Abstract: Objective: To determine the plasma triglyceride (TG) and unbound free fatty acid (FFAu) levels in infants treated with increasing dosages of soybean lipid, intralipid (IL), infusion. Study design: TG and FFAu levels were measured in 78 preterm infants (BW 500–2000 g; GA 23–34 weeks) using the fluorescent probe ADIFAB2 and enzymatic method. Results: The infants' BW was 1266.2 ± 440.7 g and GA 28.8 ± 3.1 weeks. TG levels were 77.4 ± 50 mg/dL, 140.2 ± 188 mg/dL ( p  < .04 compared to levels during low dose IL infusion) and 135.6 ± 118 mg/dL ( p  < .004), respectively during increased IL rates. FFAu levels were 17.7 ± 13 nM, 47.3 ± 102.8 nM ( p  = .07) and 98 ± 234 nM ( p  = .03). TG levels correlated with IL dose, the rate of IL administration, and FFAu levels. TG and FFAu levels were higher in infants below 28 weeks' gestation Conclusions: Increasing dosage of IL is associated with increasing levels of TG and FFAu, especially in infants below 29 weeks of gestation. The increased level of FFAu suggests inefficient cellular utilization.